Assessment of the prospects of the Dzhagdy-Selemdzinskaya gold-bearing metallogenic zone of Priamurskaya province - V. A. Stepanov; A. V. Melnikov (Известия высших учебных заведений: Геология и разведка, 2015)
Dzhagdy-Selemdzinskaya metallogemc zone is shown to be the one of the most productive gold-bearing zones in Priamurskaya province. The placer and ore deposits mined in the area are estimated to be about 350 t of gold, including 293,811 of placer and 57,191 of ore deposits. Thirteen placer ore nodes are allocated within the area (west to east): Dolbyrsky, Unya-Bomsky, Tuksinsky, Dugdinsky, Norsky, Egorsky, Malomyrsky, Verhnestoybinsky, Tokursky, Haiginsky, East-Selemdzinsky, Sophiysky and Kerbinsky. The potential of the mctallogcnic zone is in additional exploration of known gold deposits, search for new deposits and placer deposits, as well as the revaluation of waste dumps of large placers to identify the technological clusters of gold.